Pelatihan Kader Posyandu dalam Upaya Pemantauan dan Penurunan Stunting di Desa Kadubale Kecamatan Banjar Kabupaten Pandeglang - Leni Sri Wahyuni; Mega Puspa Sari (FKM UIN Sumatera Utara Medan, 2022)
Stunting is a child's growth and development disorder caused by lack of nutrition, infection, or inadequate stimulation. One of the important roles in detecting stunting at the village level is the anthropometric measurement of length or height by posyandu cadres. This PKM activity was carried out with the aim of increasing the capacity of cadres in monitoring stunting through anthropometric measurements and proper assessment of stunting status. Kadubale Village is one of the villages in Pandeglang Regency with a fairly large number of cadres, namely 40 people, and among them there are many new cadres. The method used in this PKM activity is cadre training in the form of measuring the length or height of toddlers at the posyandu and assessing stunting status using an anthropometric rotary tool that is easy for cadres to use. The result of the training that has been carried out is that there is an increase in the skills of cadres in measuring body length and height, as well as increasing skills in assessing stunting status using a nutritional status rotary tool.